Price discovery of South African stocks cross-listed on the New York Stock Exchange - K. J. Chipunza; K. R. Tsunga; Kerry McCullough (Cogent Economics & Finance, 2020)
The number of South African firms that have sought cross-listing in regional and global markets has been increasing. Many firms increase their presence beyond local markets, and one of these avenues is through cross-listing; however, it remains unclear whether the home or host market contributes more to the incorporation of information in cross-listed stocks. This study examined the price discovery process of Johannesburg Stock Exchange (JSE) domiciled stocks with a cross-listing on the New York Stock Exchange (NYSE). The price discovery of cross-listed stocks was tested using Johansen's and Phillips-Ouliaris' cointegration, the vector error correction model and common factor weights. Long-term relationships consistent with the law of one price were found. Contrary to the home bias hypothesis, results indicated that the NYSE dominated price discovery. Fund managers and investors who have included JSE cross-listed stocks in their portfolios should devote more attention to the NYSE as information flows appear to occur mainly from the NYSE to JSE. Further, results suggest that there is co-movement and integration between the USA and South Africa which diminishes diversification benefits for investors.
Keywords: 330; Cross-listed stocks; JSE; NYSE; price discovery